Better man [videorecording (DVD)] - Gracey, Michael (Film director); Gleeson, Simon, 1977-; Cole, Oliver; Williams, Robbie; Davies, Jonno; Pemberton, Steve, 1967 September 1-; Herriman, Damon, 1970-; Banno, Raechelle; Steadman, Alison, 1946- (Paramount Pictures, 2025)
Better Man is based on the true story of the meteoric rise, dramatic fall, and remarkable resurgence of British pop superstar Robbie Williams, one of the greatest entertainers of all time. Under the visionary direction of Michael Gracey (The Greatest Showman), the film is uniquely told from Robbie's perspective, capturing his signature wit and indomitable spirit. It follows Robbie's journey from childhood, to being the youngest member of chart-topping boyband Take That, through to his unparalleled achievements as a record-breaking solo artist all the while confronting the challenges that stratospheric fame and success can bring.